Proof of Element of Unlawfulness Acts in The National Criminal Code - Andre, Gusti Muhammad; Arief, Barda Nawawi; Sularto, RB; Azizah, Faiqah Nur; Nabela, Nadia (LAW REFORM, 2025)
In criminal law, unlawful acts are one of the elements of a crime. Logically, in addition to the acts formulated in the law, the unlawful act must also be proven. If an unlawful act is not proven, then an act cannot be considered a crime. However, the elements of unlawful acts regulated in the old Criminal Code differ from those in the National Criminal Code. This article aims to analyse the law of evidence in relation to unlawful acts in the National Criminal Code, in order to establish the truth of the matter. The research method used is the normative juridical method with a literature study analysis. Proving the essence of formal (written) law in the law of evidence is very easy; however, proving the essence of material law is more difficult, as it requires the judge to explore the sense of legal justice that exists in society. In criminal law, proof of unlawful acts is based on the postulate in criminalibus probantiones bedent esse lucis clariores, which states that in criminal cases, evidence must be clearer than light.